Nrf2 Knockout Affected the Ferroptosis Signaling Pathway against Cisplatin-Induced Hair Cell-Like HEI-OC1 Cell Death. (1st July 2022) - Wang, Weilong; Ma, Pengwei; Gao, Wei; Lu, Peiheng; Ding, Xuerui; Chen, Jiawei; Yuan, Hao; Lu, Lianjun
Abstract : Cisplatin is a well-known and widely used anticancer drug with high therapeutic efficacy in solid tumors; however, side effects are common with its use. Because cisplatin can be retained in the cochlea, ototoxicity leading to hearing loss limits its clinical applications. Here, we report that Nrf2 knockout (KO) strongly increased cisplatin resistance in HEI-OC1 cells, which are immortalized cells from the murine organ of Corti. The underlying mechanism of this phenomenon was uncovered, and an important novel therapeutic target for combating cisplatin-induced hearing loss was identified. Preliminary investigations determined that Nrf2 KO markedly decreased TfR1 protein levels and increased GPX4 protein levels. Thus, ferroptosis may protect organisms from cisplatin-induced cell death. Furthermore, Nrf2 KO cells were resistant to the classical ferroptosis inducers RSL3 and erastin, providing solid evidence that Nrf2 KO inhibits ferroptosis and that knocking out Nrf2 may be a new clinical strategy to prevent cisplatin-induced hearing loss.